How do the physical and physiological demands of training and official football match for recreational players compare to those of semi-professionals? - Chainok, Phornpot; Abdul, Diogo Rego; Pizarro, Andreia Isabel Nogueira; Barreira, João; Ribeiro, José Carlos; Santos, Maria Paula; dos Santos, José Augusto Rodrigues; Ribeiro, João; Ribeiro, João; Zacca, Rodrigo (Frontiers in Sports and Active Living, 2025)
Playing football at very different competitive levels can lead to different physical and physiological demands. Daily routines of these practitioners can also show differences in terms of leisure time, main professional occupations, among other activities. Therefore, understanding the physical and physiological demands between recreational and Semi-Professional players is crucial for designing appropriate training programs and assessing potential health benefits. We compared physical and physiological demands, particularly, considering external load at different heart rate (HR) intensity zones, between recreational and Semi-Professional football players by means of an ecological approach. We evaluated internal and external load related variables during i) a typical week of training and ii) a 90-min 11-vs.-11 official football match in recreational (N = 9) and Semi-Professional teams (N = 7). The measures were collected using wearable technologies (high-frequency GPS tracking and inertial devices). Semi-Professional players performed more training sessions·week−1 (4 vs. 2) and are likely to be involved in 26.2% higher weekly vigorous physical activity volume (min·week-1) (95%CI: 49.2–87.5 min·week-1; p = 0.050; ɳp2 = 0.175; small effect) than recreational practitioners, despite any other type of professional occupation. Mean pre-match baseline HR was 17% lower in Semi-Professional than recreational group (p = 0.003; ɳp2: 0.475; moderate effect). Likewise, mean HR reserve was 12% higher in semi-professional than recreational players (p = 0.002; ɳp2: 0.–0.551; moderate effect). Mean HR values during 90 min 11-vs.-11 official football match were 80 ± 6%HRmax (Semi-Professionals; N = 7) and 81 ± 5%HRmax (recreational; N = 9), respectively (diff: −1%; 95%IC: −7.8 to 4.9%; p = 0.630; ɳp2: 0.017). Semi-Professional players covered 41% more distance at high HR (>85% HRmax) (95% CI: 211–5,103 m, p = 0.035, η² = 0.279; moderate effect) during 11-vs.-11 official football match, suggesting greater cardiorespiratoy fitness when compared to recreational players. At last, the distance covered at 70%–80% HR level was positively associated with the % at very vigorous physical activity levels in training (p = 0.033; r = 0.533). These findings suggest that recreational players may require modified training protocols to optimize performance while managing internal load.